A longitudinal evaluation of bone mineral density across a macrocycle in highly trained female athletes: a systematic review - Black, G. M.; Wells, M.; Devlin, B. L. (Sports, 2026)
Bone health in highly trained female athletes is critical for performance and long-term wellbeing, yet systematic evidence regarding seasonal changes remains limited. The main objective of this systematic review (PROSPERO ID: 420251230393) is to determine changes in bone mineral density (BMD) and bone mineral content (BMC) across the sport macrocycle in highly trained female athletes, encompassing both elite and collegiate (NCAA) populations. Six databases were searched for studies published between 2010 and 2025, with inclusion requiring female athletes, BMD/BMC measurements, and longitudinal assessment across a macrocycle. Fourteen studies involving 522 premenopausal athletes were included, with dual-energy X-ray absorptiometry measurements conducted approximately six months apart. Study quality was assessed using the NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies and indicated a predominantly good quality. Five studies reported no significant change in BMD/BMC, five demonstrated improvements, three reported mixed findings across sports or athlete subgroups, and one reported a significant decline. Only two studies attempted to account for all three primary confounders—menstrual cycle status, dietary intake, and physical activity monitoring—while seven reported no confounding variables. While bone health appears largely maintained across the sport macrocycle in highly trained premenopausal female athletes, these findings should be interpreted cautiously given the inadequate confounder reporting, heterogeneous sport exposures, variability in skeletal sites measured, and inconsistent measurement timing. Future research must comprehensively assess these variables alongside sport-specific skeletal measurements to identify athletes at risk of bone health deterioration.